An analytical approach of multi-dimensional Navier-Stokes equation in the framework of natural transform - Manoj Singh; Ahmed Hussein , Msmali; Mohammad Tamsir; Abdullah Ali H. Ahmadini (AIMS Mathematics, 2024)
This article introduces a new iterative transform method and homotopy perturbation transform method along with a natural transform to analyze the multi-dimensional Navier-Stokes equations. To solve the fractional-derivative, the Caputo-Fabrizio definition of the fractional derivative was employed. Four examples were considered to examine the efficacy and accuracy of the proposed methods. The efficiency and accuracy were also demonstrated by the solution comparison via graphs. The proposed methods' convergence and uniqueness are also discussed. The methods mentioned above are straightforward and support a high rate of convergence.